Secreted frizzled-related protein 4 (SFRP4) and fractalkine (CX3CL1) — Potential new biomarkers for β-cell dysfunction and diabetes - Bergmann, Katarzyna; Sypniewska, Grazyna (Clinical biochemistry, 2014)
The discovery of new risk factors for diabetes is a major challenge for contemporary science. Pathogenesis of type 2 diabetes mellitus (T2DM) is closely related to adipose tissue dysfunction. The aim of this review was to describe recently discovered cytokines: fractalkine (CX3CL1, FKN) and secreted frizzled-related protein 4 (SFRP4) as potential biomarkers of early β cell dysfunction and diabetes. The association of CX3CL1 and SFRP4 with low-grade inflammation in adipose tissue links obesity with disturbances in insulin secretion and impaired glucose metabolism, therefore it indicates new therapeutic and preventive targets in both healthy and diabetic subjects. •T2DM pathogenesis is related to low-grade inflammation and adipocyte dysfunction.•We reviewed data on new potential biomarkers of β cell dysfunction: SFRP4, CX3CL1.•SFRP4 and CX3CL1 levels might be increased several years before the onset of T2DM.•Diagnostic and clinical utility assessment of new biomarkers for T2DM is required.